Digital Economy 2047: Transforming India Through Startups and Innovation - Anand Mallikarjun (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
India’s aspiration to become a developed nation by 2047 is closely tied to the expansion of its digital economy. The rapid rise of startups, along with technological innovation and supportive government policies, has accelerated the country’s transition from a traditional, resource-based economy to one driven by knowledge and innovation. Startups have become key players in creating employment, fostering financial inclusion, and introducing disruptive technologies across sectors such as healthcare, education, agriculture, and fintech. This paper examines the transformative potential of the digital economy by analysing historical trends, current developments, and future prospects. It highlights how digital entrepreneurship contributes to inclusive growth, global competitiveness, and sustainable development, while also addressing challenges such as the digital divide, regulatory hurdles, and limited R&D investment. Projections suggest that startups will play a decisive role in shaping India’s innovation-led growth trajectory and positioning the nation as a global digital leader by 2047.